ANALISIS FAKTOR YANG MEMPENGARUHI PROFITABILITAS PT PEGADAIAN (PERSERO) PERIODE 2001-2015 - NABILA CLAUDIA A.; Sugeng Hariadi; Mintarti Ariani (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to examine and analize the effect of Current Ratio, Owner's Equity to Asset, and Total Assets Turn Over on Return On Equity (ROE) in PT Pegadaian (Persero). These ratios can examine the wellness of PT Pegadaian (Persero). Return On Equity (ROE) is the dependent variable, whereas Current Ratio, Owner's Equity to Asset, and Total Assets Turn Over are the independent variables. The data used is annual financial reports of PT Pegadaian (Persero) from 2001 – 2015. This empirical study use a quantitative approach and method of OLS (Ordinary Least Squares). The result of this research indicate that Current Ratio has negative and statistically insignificant effect on Return On Equity; Owner's Equity to Asset has negative and statistically significant effect on Return on Equity; Total Assets Turn Over has positive and insignificant effect on Return on Equiy.